Digital user rights and their enforcement: What is the copyright directive asking for? - Jasmin Brieske (The Journal of World Intellectual Property, 2023)
Art 17 Directive 2019/790 on copyright and related rights in the Digital Single Market (CDSMD) offers not only a new perspective on service provider liability but also on user rights in the digital sphere of copyright law. The Directive obliges Member States to enable users of online content sharing service providers to assert the use of an exception or limitation before a court or another judicial authority. Hence, art 17 CDSMD foresees a subjective, that is, enforceable, right of the user deriving out of the exceptions and limitations of copyright and related rights. Yet, there is no clear guidance on how to transpose this requirement into national law, neither in art 17 CDSMD nor within the judgment of the CJEU in the annulment proceeding or the guidance of the EU Commission. This generates uncertainty for Member States, for which the concept of enforceable user rights is novel. The paper examines the requirements which art 17 CDSMD sets out for digital user rights and the difficulties for Member States to comply with them. The example of the German transposition of art 17 CDSMD shows that a high standard of user protection is not necessarily accompanied by a respective enforceability mechanism.
Keywords: 340; CDSM Directive; exceptions and limitations; filtering technologies; freedom of expression and information; platform regulation; user rights